Antimicrobial Impact of Wood Vinegar Produced Through Co-Pyrolysis of Eucalyptus Wood and Aromatic Herbs - Gil Sander Próspero Gama; Alexandre Santos Pimenta; Francisco Marlon Carneiro Feijó; Caio Augusto Martins Aires; Rafael Rodolfo de Melo; Caio Sérgio dos Santos; Lúcio César Dantas de Medeiros; Thays Vieira da Costa Monteiro; Maíra Fasciotti; Priscila Lira de Medeiros; Maria Rita Macêdo de Morais; Tatiane Kelly Barbosa de Azevedo (MDPI AG, 2024)
Background: The search for substances that can overcome microorganisms' resistance and enhance the antimicrobial activity of given products has attracted the attention of researchers. Eucalyptus wood vinegar (WV) is a promising product for developing alternative antimicrobials. Objectives: This study aimed to evaluate whether the production of WV in the co-pyrolysis of eucalyptus wood with aromatic herbs would incorporate compounds from them into WV and if that would enhance its antimicrobial action. Methodology: WV was produced alone and through co-pyrolysis with marjoram (Origanum majorana), Peruvian oregano (Origanum vulgare), rosemary (Salvia rosmarinus), thyme (Thymus vulgaris), and Turkish oregano (Origanum onites) at a proportion of 25% of herbs to the bone-dry wood weight. The antimicrobial effects were assessed against strains of gram-negative and -positive bacteria, and Candida glabrata. Microorganisms' colony growth in agar had their absorbances recorded after inoculation and incubation. Chemical characterization of the new products was performed by gas chromatography and mass spectrometry (GC/MS). Results: After coproduction, there were relevant chemical changes concerning the original WV. Thymol, for instance, was incorporated into the WV through co-pyrolysis with marjoram, Peruvian and Turkish oregano, and thyme. The coproducts were more efficient than the WV produced only with wood, with thyme-incorporated products having the highest efficiency. This can be attributed to the increase and incorporation of the substances after coproduction, and particularly the role of thymol in enhancing the antimicrobial action. Conclusion: Given the results, the co-production of WV with eucalyptus wood and aromatic herbs has the potential to provide alternative antimicrobial products.